Learning of special course «Basics of scientific organization of students’ academic work» as a condition of the effectiveness of educational process (Pedagogy of Higher and Secondary Education, 2013)
Topol’nik Y. V. Learning of special course «Basics of scientific organization of students’ academic work» as a condition of the effectiveness of educational process.In the article considers aspects of the problem of scientific organization of educational work of students of pedagogical university. Indicated that the requirements of scientific organization of work cover all aspects of life as in the field of learning activities of students, as and in their free time. It is noted that future teachers should master the basics of the scientific organization of pedagogical work, skills of scientific organization of work schoolchildren. Attention is drawn to the fact that the best learning results can be achieved with provided by a combination of the formation of a special study course of training skills to the teaching of specific subjects of psycho-pedagogical cycle. The main provisions of the program developed by the author of the special study course.
Keywords: special study course; scientific organization of educational work; educational work; knowledge; competencies; skills; future teacher